TOURISM RECOVERY STRATEGY AFTER COVID-19 PANDEMIC (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2021)
AbstractThe Covid-19 pandemic has resulted turbulence in all sectors. The rapid spread of the virus has caused the government to quickly adopt policies. The tourism sector is a sector that has been severely shaken due to this pandemic. The tourism sector and its supporting industries have almost collapsed and their activities have stopped. This study is aimed to determine the recovery strategy for the tourism sector and the creative economy of Padang City after the Covid-19 pandemic. This research is a descriptive qualitative study with data collection techniques by using the triangulation method: the collection of research data that is using observation techniques, in-depth interviews and document analysis. The result of this research is that the recovery strategy of the tourism sector and the creative economy in Padang City is carried out by rehabilitating and maintaining infrastructure, revitalizing both destinations and attractions, and creative economy businesses as well as promotion to stimulate the tourism sector.